Implementasi Framework ISO 31000 dalam Pengelolaan Risiko UMKM Percetakan Palugada Printing di Kota Bandung - Afrian Insan Kamil; Fatimah Rahman; M Ramadhika Gautama K; Muhamad Zaki; Alfiana (Indo Publishing, 2025)
This study uses Palugada Printing as the object of study, which is a small-medium-scale MSME engaged in printing and product branding services. The purpose of this study is to assess various risks that hinder the achievement of Palugada Printing's business objectives and determine the best treatment for possible risks. This study uses a Qualitative Descriptive method and applies the ISO 31000 Framework analysis to carry out the process of risk identification, risk analysis, risk evaluation, and risk treatment, with the help of the Risk Management Matrix in assessing risk levels. The results of this study indicate that there are 6 main types of risks with a total of 13 risk events, including 4 events with Low Risk Level, 5 events with Medium Risk Level, and 4 events with High Risk Level that require special attention, limited business capital, lack of labor, not yet registered trademarks and designs to the HAKI system, and unstable cash flow. These findings emphasize the importance of implementing systematic risk management for MSMEs in the printing sector in order to improve operational stability, financial efficiency, and competitiveness amidst increasingly fierce digital competition.